2022
DOI: 10.1111/asap.12307
|View full text |Cite
|
Sign up to set email alerts
|

Economic contact in service encounters between groups in protracted conflict

Abstract: The study examines whether qualitative and quantitative characteristics of intercultural service encounters (ISEs) between majority customers and ethnic minority service providers are associated with better attitudes toward the entire minority group. The study was conducted in Israel through an online survey of 402 respondents. The study revealed that the customers derived pleasure from high perceived value of services and from taking advantage of a good deal. This pleasure, in turn, was positively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 116 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…These studies (Yustisia 2016;Yustisia and Hudijana 2021) exhibited a good consistency of GES's α between 0.80 to 0.89 (Kottner et al 2011;Saliasi et al 2021). Other studies have employed the GES with a 5-point scale, demonstrating a satisfactory reliability (Kushnirovich and Lissitsa 2022;Mazziotta et al 2015). In another study, the GES was utilized with an 11-point scale, yielding an α value of 0.96 (Healy et al 2017).…”
Section: Internal Consistencymentioning
confidence: 86%
See 3 more Smart Citations
“…These studies (Yustisia 2016;Yustisia and Hudijana 2021) exhibited a good consistency of GES's α between 0.80 to 0.89 (Kottner et al 2011;Saliasi et al 2021). Other studies have employed the GES with a 5-point scale, demonstrating a satisfactory reliability (Kushnirovich and Lissitsa 2022;Mazziotta et al 2015). In another study, the GES was utilized with an 11-point scale, yielding an α value of 0.96 (Healy et al 2017).…”
Section: Internal Consistencymentioning
confidence: 86%
“…In Wright et al (1997) study the six items of the GES were unidimensional constructs and had a reliability alpha Cronbach of 0.90. Other researchers also found that the GES has very good internal consistency reliability estimates (Kushnirovich and Lissitsa 2022;Vezzali et al 2023).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…As such, this hypothesis which was developed into intergroup contact theory (Pettigrew & Tropp, 2006; Pettigrew, 1998) is considered as one of the most effective psychological strategies for improving intergroup relations (Dovidio et al, 2003, p. 5). Often, however, the problem is how to implement direct contact, for example in segregated areas where the chances of such contact are rare, or when a specific outgroup is perceived as especially threatening (Hewstone et al, 2008; Kushnirovich & Lissitsa, 2022). Evidence from multiple sources indicates that in such cases the character of intergroup relations may be predicted by indirect contact of the type that does not require real intergroup encounters but still manages to transmit information about outgroup members (Dovidio et al, 2011; Vezzali et al, 2014; White et al, 2020).…”
Section: Introductionmentioning
confidence: 99%